Penegakan Hukum dan Implikasi Hukum Tindak Penganiayaan Berdasarkan Pasal 351 KUHP - Widjaja, Gunawan; Damun, Damun (CV. Creative Tugu Pena, 2024)
Law enforcement against acts of abuse, as regulated in Article 351 of the Criminal Code, has significant implications in the context of justice and protection of individuals. Effective law enforcement requires thorough investigative steps, the collection of strong evidence, and the firm prosecution of perpetrators of violence. Protection of victims is the main focus in this law enforcement process, which includes physical, psychological and legal aspects. The importance of providing holistic support to victims, including access to health services and adequate legal protection, cannot be overstated. Fairness in handling cases is also very important, with an emphasis on fair and transparent legal principles. The judge must be able to weigh the evidence objectively and make a decision in accordance with the law. Apart from that, prevention and rehabilitation efforts also have a crucial role in reducing incidents of abuse. Through public education, prevention campaigns and rehabilitation programs for perpetrators of violence, it is hoped that a safer and more empowering environment can be created for all individuals. Thus, law enforcement and legal implications for acts of abuse based on Article 351 of the Criminal Code emphasize the importance of cooperation between law enforcement agencies, government, non-governmental organizations and society in creating an environment free from violence and protecting the human rights of every individual. Keywords: Law Enforcement, Legal Implications, Persecution, Article 351 of the Criminal Code.